Employee Spirit: The Influence of Leadership Style and Work Environment: Study on Education and Culture Service Serang District - Rohaelis Nuraisiah; Anggi Haerani (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2022)
The method used in this study is quantitative. This method uses to predict the influence between the independent variable and the dependent variable; in this study, the variable X1 (Leadership Style), X2 (Work Environment) is the independent variable and the variable Y (Work Spirit) is the dependent variable. The sample in this study was 70 people; the instrument used was primary data, and multiple linear regression analysis uses to analyze the data. Based on the results of the study, there is a significant influence between leadership style and work environment on employee morale at the Education and Culture Office of Serang Regency. With the test results obtained multiple linear regression equation Y= 28.019 + 0.215 X1 + 0.246 X2. and hypothesis testing, the value of tcount Leadership Style = 2.312, using the significant limit = 0.05, obtained ttable = 1.66757. Moreover, tcount Work Environment = 4.034 obtained ttable = 1.66757. The test criteria from these results are tcount > ttable, meaning H0 reject, and H1 is accepted. Thus, the t-test hypothesis of the leadership style variable and work environment significantly influence work motivation. The leadership style variable has a coefficient of determination of 0.215, which means there is an influence of leadership style. It works environment on employee morale by 21.5%, and the remaining 78.5% influenced by variables others not included in this study.